Alternative provision: the surge in demand and the role of remote online learning in creating capacity - Sharon Smith (Quality Education for All)
Purpose – The surge in demand for alternative provision (AP) necessitates that school leaders and educational practitioners overcome considerable challenges to secure high-quality, high-impact provision for a vulnerable and complex cohort of school-aged learners. The purpose of this study is to examine the national context based on secondary data analysis, before exploring the perspectives of leaders and practitioners on the use of remote online learning as a model for meeting demand. Design/methodology/approach – Having examined the national data available, grass-roots perspectives were gleaned through an exploratory research model. Survey and focus group data was thematically analysed to distil perspectives on the uses and challenges of remote online learning to create capacity. Findings – The findings of this study indicate considerable scope and potential for remote online learning as model for suitable and sustainable AP. However, there are challenges that mirror face-to-face provisions and should not be overlooked. Remote online learning does not offer a universal solution, but a viable option that can be deployed using professional judgement and an understanding of individual student needs. Originality/value – This exploratory paper contributes secondary analysis of the national data available, offers insights on the reasons for the demand for AP and highlights the challenges faced by those working within the sector. This study offers practitioner perspectives from those pioneering the use of remote online learning in AP.